Jak nas widzą… Panorama z Kołem Polonistów (w tle) - Telicki, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article is an attempt at a critical review of Adela Kobelska’s study Miasto. Uniwersytet. Literaturoznawstwo. Poznań lat dwudziestych i trzydziestych XX wieku jako przestrzeń działania członk.w Koła Polonist.w [The City. The University. The Literary Studies. Poznań in 20. and 30. of XX Century as a Space for Activities of Polish Language and Literature Student’s Associaition]. Questions asked for the author and polemics against some thesis of her discourse are centered around both historical and methodological problems (the last one may be named geopoetics of intelectual movements). The article is also an attempt to confront the inside and outside view of Polish Studies at Adam Mickiewicz University in Poznań.